The Effect of Feedback as Soft Scaffolding on Ongoing Assessment Toward The Quantum Physics Concept Mastery of The Prospective Physics Teachers (Jurnal Pendidikan IPA Indonesia, 2018)
Many recent studies have reported that feedback plays a very important role in students’ learning outcomes. However, currently, feedback has not been utilized by lecturers and students in the learning process effectively. This study aimed to explore the impact of feedback as a soft scaffolding in the ongoing assessment of Quantum Physics class for the students as prospective Physics teachers. A quasi-experimental design non-equivalent pretest-posttest control group was used to examine the effectiveness of feedback based on ongoing assessment. The results of the study revealed that students who received feedback based on metacognitive and social constructivism on studying Quantum Physics showed better average results compared to students who received traditional feedback based on the cognitivism in the form of correction.